TRANSIENT CHANGES IN EXTRINSIC FLUORESCENCE OF NERVE PRODUCED BY ELECTRIC STIMULATION - Tasaki, I. (1969)
Nerves stained with one of the following fluorochromes were found to respond to electric stimulation with transient changes in the fluorescent light: acridine orange, acridine yellow, 8-anilinonaphthalene-1-sulfonate, auramine O, 1-dimethylaminonaphthalene-5-sulfonyl chloride, fluorescein isothiocyanate, LSD, pyronin B, pyronin Y, rhodamine B, rhodamine G, rose bengal, and 2-toluidinylnaphthalene sulfonate. The properties of covalently bonded fluorochromes in the nerve and the behavior of fluorochromes introduced into the axon interior were studied. By measuring fluorescence polarization, direct evidence was obtained showing a decrease in intramembrane viscosity during the action potential.